Pembangunan Kakas Bantu Pencarian Lokasi Fitur dalam Source Code menggunakan Metode Latent Semantic Indexing - Muhammad Iqbal Alvin Harlia Rahman; Achmad Arwan; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Features in the software are functions that result from the functional requirements of a system and can be triggered by the user. Features are the result of the implementation of the functional requirements of a system. Every software must be maintained or repaired to maintain its quality and performance. The improvements made are related to feature changes or the addition of functions to certain features. However, in fixing a specific feature it takes time to find the location of the feature. The process of searching for features is generally carried out by programmers using the simple search feature that matches the keywords entered in each section of the class. This search process takes a long time if applied to a program code that has a large size and is separated into many classes. To solve this problem, a system was created to help programmers locate certain features in the program code using a desktop-based system. The process of developing this system uses the SDLC waterfall. Implementation is carried out using the C Sharp programming language and using the Visual Studio framework which implements object-oriented development. The results of the testing phase resulted in 20 valid test cases and testing of the efficiency of the search time got results of more than 80%, which indicates that the software can be used to find the features the user wants.